2000
DOI: 10.1029/2000jb900159
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics and denudation adjacent to the Xianshuihe Fault, eastern Tibetan Plateau: Constraints from fission track thermochronology

Abstract: The Xianshuihe‐Xiaojiang fault system extending from eastern Tibet to central Yunnan, China, is a major left‐shear structural boundary, accommodating the clockwise rotation of crustal rocks between the Eastern Himalayan syntaxis and the South China Block. Zircon and apatite fission track (FT) data are reported for 111 samples of basement collected from both sides of the northern part of this fault and spanning 300 km across the eastern margin of the Tibetan Plateau, where its mean elevation drops from 3500 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
147
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(167 citation statements)
references
References 44 publications
17
147
3
Order By: Relevance
“…Cenozoic denudation has been heterogeneous across the eastern margin of the plateau adjacent to the Sichuan Basin, with high rates focused in a narrow zone along the present topographic front. These results are broadly consistent with the distribution of denudation inferred from apatite and zircon fission track ages in the Longmen Shan region [Arne et al, 1997] and along the margin of the plateau south and west of the Xianshuihe fault [Xu and Kamp, 2000].…”
Section: Rates and Pattern Of Denudationsupporting
confidence: 78%
See 3 more Smart Citations
“…Cenozoic denudation has been heterogeneous across the eastern margin of the plateau adjacent to the Sichuan Basin, with high rates focused in a narrow zone along the present topographic front. These results are broadly consistent with the distribution of denudation inferred from apatite and zircon fission track ages in the Longmen Shan region [Arne et al, 1997] and along the margin of the plateau south and west of the Xianshuihe fault [Xu and Kamp, 2000].…”
Section: Rates and Pattern Of Denudationsupporting
confidence: 78%
“…Thus the variation in cooling ages between the topographic margin of the plateau and the interior appears to be a robust feature of both the apatite and zircon (U-Th)/He data. Similar variations in apatite fission track ages were observed in the Longmen Shan [Arne et al, 1997] and to the south, along the Xianshuihe fault [Xu and Kamp, 2000].…”
Section: (U-th)/he Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…For example, Clift and Sun (2006) suggested that the sedimentation rates in the Y-SH Basin increased sharply at the end of the Miocene. Clark et al (2005) used an initiation of the major river incisions to identify the timing of the initial uplift at 13e9 Ma and the high erosion rates between 0.23 and 0.47 mm/yr, and the result does coincide with the thermochronology data published by Xu and Kamp (2000) and Kirby et al (2002). Gong and Li (2004) found that the uplift of the Tibetan Plateau since 10 Ma has had an important influence on the climate and sedimentary environment of the South China Sea, and the thick infill of the Y-SH Basin has been supplied by paleo-Red River delta during the Late Miocene.…”
Section: Tectonic Implicationmentioning
confidence: 61%